Evolution of damage under combined low and high cycle fatigue loading in a type 316LN stainless steel at different temperatures. (October 2017) - Sarkar, Aritra; Nagesha, A.; Parameswaran, P.; Sandhya, R.; Laha, K.; Okazaki, M.
Highlights: Cyclic life ( Nb ) decrease with increase in the temperature and block size ( Bs ). Dynamic strain aging (DSA) supressed ratcheting strain accumulation. Significant strain accumulation took place at 923 K through ratcheting and creep. Fracture mode in CCF is through LCF (striations), creep (intergranular facets) or ratcheting (dimples). HCF damage acts as an catalyst by linking up intergranular creep cracks and transgranular LCF cracks. Abstract: The present study investigates the effect of different damage modes like low cycle fatigue (LCF), high cycle fatigue (HCF), creep and ratcheting during combined cycling at various temperatures ranging from ambient to 923 K, in a type 316LN austenitic stainless steel. The experiments were designed with multi-step load sequences where specific number of small amplitude HCF cycles (referred to as blocks ) were introduced at the stabilized cyclic load under LCF for a given strain amplitude and repeated until failure. Cyclic life was found to decrease with increase in temperature as well as block-size. The decrease in cyclic life with block-size is more significant at 923 K where multiple damage modes like creep and ratcheting are activated. Dynamic strain aging (DSA) was found to operate in the temperature range, 823–873 K where the decrease in cyclic life with block-size gets saturated. Typically, transgranular fatigue fracture, intergranular creep fracture or dimpled rupture was identified when failure was dictated by LCF, creep and ratcheting respectively. However, synergistic interaction between the above damage modes leading to a mixed mode fracture carrying signatures of fatigue striations, intergranular facets and dimples occurred at specific combinations of block size and temperature. HCF damage played an important role for some specific loading conditions by acting as a link between intergranular (creep) cracks, thus facilitating the crack propagation and final failure. The regimes of dominant failure modes and interactions among them were suitably mapped as a function of temperature and block size.